TRADISI UANG JAPUIK DAN UANG ILANG DALAM SISTEM PERKAWINAN DI NAGARI TANDIKEK KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN - Hafizah Hafizah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
Study aims to reveal the process tradition pinch money andlose mone , meaning contained in the tradition of the pinch money and lose money, internal conflicts that occur due to tradition pinch money and lose money, and resolve conflicts that occur. This type of research is the kind of case study. The dwarf selection method using the informant (purposive sampling). The results showed that the process of payment of pinch money and lose money in marriage system in the Tandikek territory Patamuan district of Padang Pariaman regency is determined by both parties submitted by uncle of female to uncle of male. After marrying pinch money will be refunded to the women when visiting parent in law. While lost money not returned again. The meaning contained in this tradition is the pride for the male, and material assistance to parents of groom. Not rarely the marriage null and void because the pinch money not able by the family of the woman, so that internal conflicts often occur with families because of the adamant to get married. Efforts are being made to reduce conflict (1) should the existence of socialization from the right to the prospective bridegroom to bride helped in giving pinch money so that the wedding can take place. (2) Should the existence of written rules regarding Nominal pinch money and lost money in Tandikek territory